Det Eviga Evangeliet - Jayne Svenungsson (Lychnos, 2012)
Taking its departure in the 19th-century idea of a “religion of humanity”, this article explores the ideological roots of this powerful vision of a new, higher religion including all human beings regardless of nationality or confession. The vision is highlighted by a close reading of Novalis’ famous text “Die Christenheit oder Europa” and the final lecture of the late Schelling’s philosophy of revelation. Through the analysis of these texts, a number of metaphors are uncovered, which, in the next section of the article, are traced back to the trinitarian theology of history of the 12th-century Calabrian abbot Joachim of Fiore. However, the aim of the article is not only to illustrate the continuity of the Joachimite legacy and the Romantic notion of a religion of humanity. Thus, in the last section I also attempt to problematize the central metaphors underpinning this notion by relating them to their wider Wirkungsgeschichte in the European politico-philosophical heritage.